2001
DOI: 10.1590/s0004-282x2001000200010
|View full text |Cite
|
Sign up to set email alerts
|

Dilatação dos espaços de Virchow-Robin em pacientes com migrânea

Abstract: No passado, acreditava-se que os espaços de Virchow-Robin (EVR) eram invaginações dos espaços subaracnóides 1,2 . Estudos com microscopia eletrôni-ca, sugerem que os EVR originam-se de invaginações do espaço subpial, formando uma bainha de revestimento que contém as artérias separando o espaço subaracnóide do subpial 3,4 .A dilatação dos EVR é facilmente detectada pela ressonância magnética (RM) 5 e tem sido descrita em pacientes com criptococose 6 , mucopolissacaridose 7 , crianças com cefaléia 8 , envelhecim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Our study, which utilized a 3T MRI device to investigate the Chinese adult migraine population, is consistent with two earlier studies that used a 1.5T MRI device, indicating the involvement of EPVS in migraine. For instance, the first study focused on a migraine population aged 13–56 years and observed a widening of the VRS in 28 (40.00%) patients with migraine compared with only 5 (7.10%) in the controls 15 . Moreover, the second study observed accentuated VRS in 61.00% of children with migraine aged 3–14 years, but only in 22.00% of children with TTH and 27.00% of children without headaches 16 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study, which utilized a 3T MRI device to investigate the Chinese adult migraine population, is consistent with two earlier studies that used a 1.5T MRI device, indicating the involvement of EPVS in migraine. For instance, the first study focused on a migraine population aged 13–56 years and observed a widening of the VRS in 28 (40.00%) patients with migraine compared with only 5 (7.10%) in the controls 15 . Moreover, the second study observed accentuated VRS in 61.00% of children with migraine aged 3–14 years, but only in 22.00% of children with TTH and 27.00% of children without headaches 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Normal PVS are not visible on MRI; MRI‐visible enlarged perivascular spaces (EPVS) provide us with a non‐invasive method of indirectly reflecting the dysfunction of glymphatic drainage, 14 which could be widely used in clinical practice. Several prior studies have focused on the relationship between EPVS and migraine 15–18 . For instance, one of these studies found that accentuated Virchow‐Robin spaces (VRS) were significantly more common in children with migraine than in those with tension‐type headache (TTH) or headache‐free controls 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Machado Jr. et al (2001) found that between equal numbers of age-matched patients suffering from migraine of unspecified subtypeand and headache-free controls ranging from adolescence to middle age, 40% of migraine patients showed enlarged PVS compared to only 7.1% of controls. 49 After comparing migraine of unspecified subtype in pediatric patients to adult patients with post-pubertal migraine onset, Schick et al (1999) showed that 61% of pediatric migraineurs had larger clusters of PVS compared to only 27% of pediatric controls and 13% adult migraineurs. 6 In contrast to these findings and other prior studies, a more recent investigation by Husøy et al (2016) discovered a decrease in PVS quantity for MWoA patients in the basal ganglia (BG) and hemispheric white matter (HWM); additionally, they showed only small differences in PVS number between headache groups and headache-free patients, as well as finding no significant association between PVS and headache category, frequency, or disease duration.…”
Section: Perivascular Spaces (Pvs)mentioning
confidence: 99%
“…The correlation between migraine and VRSs has rarely been studied previously, and only two studies have investigated the relationship between migraine and VRSs in (Husøy et al, 2016;Machado et al, 2001a). Machado et al first found that there were more expanded VRSs in migraineurs than in normal controls (Machado et al, 2001a).…”
Section: Risk Factors For Mri Abnormalities In Migraine Patientsmentioning
confidence: 99%
“…The correlation between migraine and VRSs has rarely been studied previously, and only two studies have investigated the relationship between migraine and VRSs in (Husøy et al, 2016;Machado et al, 2001a). Machado et al first found that there were more expanded VRSs in migraineurs than in normal controls (Machado et al, 2001a). In contrast, the HUNT-MRI study found no significant difference between the migraine and control groups, and even fewer VRS numbers in migraineurs without aura than in controls (Husøy et al, 2016).…”
Section: Risk Factors For Mri Abnormalities In Migraine Patientsmentioning
confidence: 99%